Clinical Trial: Management of Post-Haemorrhoidectomy Wound Healing by Bergamot Flavonoid-Based Gel and Sodium Hyaluronate: An Observational, Multicentric Trial - Cafaro, Danilo; Onofrio, Luciano; Sturiale, Alessandro; Puglia, Salvatore; Sinicropi, Maria Stefania; Catalano, Alessia; Naldini, Gabriele (Journal of Pharmacy and Nutrition Sciences, 2023)
Objective: Haemorrhoidal disease (HD) is a very diffuse anorectal condition that involves a large part of the population, both male and female of every age. Among the procedures proposed to treat HD, conventional excisional surgery remains one of the most performed. Milligan-Morgan (MM) technique is one of the most used haemorrhoidectomy techniques. In this technique, the wounds are left open and re-epithelialization requires almost 3-5 weeks, in which patients generally experience pain and intense discomfort improving over the weeks. Methods: The aim of this study was to evaluate the effect of topic administration of Benebeo Gel®, mainly composed by bergamot-derived flavonoids and hyaluronic acid, on post-operative wound healing after open MM haemorrhoidectomy. An observational prospective study was carried out, involving 205 patients aged between 18 and 75. Results and Conclusion: The results after 2 weeks of treatment seem to be promising with a very good clinical outcome and patient satisfaction within 1 month.